Circulating microparticles in normal pregnancy and pre-eclampsia. - Redman, C; Sargent, I (2008)
Cellular particles may be larger shed microparticles (>or=100 nm, MPs) that are the products of cell activation or necrosis. There are also smaller endocytic nanoparticles (<100 nm), called exosomes, which are internal vesicles of late endosomes or multivesicular bodies and are released into the extracellular milieu upon fusion of the multivesicular body with the cell surface. Both MPs and exosomes can be detected in the circulations of non-pregnant and pregnant women. In the former MPs are increased in conditions associated with systemic inflammation such as sepsis or metabolic syndrome. During normal pregnancy MPs are increased and they increase further with pre-eclampsia. They include not only MPs derived from platelets, endothelium and various leukocytes but also syncytiotrophoblast derived MPs (often called STBMs). STBMs interact with both immune and endothelial cells and may contribute to the systemic inflammation of both normal and pre-eclamptic pregnancies. However inhibitory activity has also been ascribed to trophoblast derived exosomes. In vitro, they down-regulate T cell activity, a T cell change that has been repeatedly observed, ex vivo, during normal pregnancy.